A case study on weed management awareness in Kampar: Farmers’ perceptions, weed flora composition, and effect of fertilizers on weed growth - Tong, Pei Sin (2024)
Rural farming is a prominent feature in developing countries. Weed management remains a challenge in food security and sustainable agriculture in the tropics, especially for smallholders. Smallholders contribute to 13 out of the 17 Sustainable Development Goals (SDGs) in economic, environmental and social contexts. The chemical approach has widespread use but the approach has risks on the environment and food safety. This study was motivated by the importance of agricultural activities in Kampar, Malaysia, but little is known about the essential aspects related to sustainable weed management for smallholders. This study addressed knowledge gaps in weed management by using Kampar as a case study and shedding light on developing a model for sustainable weed management for smallholders. A semi-structured questionnaire survey was designed to study and glean rural farmers’ knowledge and perception of weeds, their sources of information, and their reasons for willingness or unwillingness to adopt non-chemical weed control methods. This survey was conducted from June to October 2018 and analysed using descriptive and chi-square statistics. Knowledge of weed species led to the anticipation of yield loss and exploration of potential control methods. It was found that social networking and agriculture chemical companies were the main sources of information on weed control methods. Despite knowing the harmful effects of chemical herbicides, farmers’ willingness/resistance to adopt non-chemical control methods depended on many different factors. Next, field surveys of weed on maize farms were conducted during June of 2017, 2018 and 2020 in a former tin mining land, with a total of 120 quadrats of 0.5 m x 0.5 m. Fifteen species were observed. Four species with the highest density were Cyperus sp., followed by Amaranthus viridis, Eleusine indica and Hedyotis corymbosa. The Shannon- Wiener diversity index (H´) showed low species diversity of weeds, while Pielou’s evenness index and Simpson’s dominance index indicated the phenomenon of non-dominating weed species on maize farms. The variation in the number of individuals in broadleaf, sedge and grass was significant between 2017 and 2018; 2018 and 2020; and 2017 and 2020. The relationship between maize, mean rainfall, mean temperature and weed species was analysed using a general linear model, and none of them affected maize yields. Based on the above information, Amaranthus viridis, being the second highest density weed found on the maize farms, was chosen for a study on plant responsiveness. The species had a high correlation in Pearson’s correlation (r) and regression (R2) between the number of inflorescences, the number of leaves, and plant heigh under treatments NPK 12:12:17, NPK 15:15:15 and in the wild respectively. Plants under NPK 12:12:17 and NPK 15:15:15 were studied with five treatments, which were control, 1 g, 2 g, 4 g and 8 g. One-way ANOVA showed that parameters of leaves and inflorescences were statistically significant at p < 0.05 for A. viridis under NPK 12:12:17, while plant height was statistically significant at p < 0.05 under NPK 15:15:15. Based on the data collected, a model for sustainable weed management for smallholders would involve a few components. The first component comprises rural farmers’ learning on weed management through insights into weed management practices among smallholders, and challenges that demand attention and efforts towards improvement for existing weed control, which is predominantly chemical herbicides. Weed composition and crop yield need to be assessed for the impacts of weeds on crop yield for monitoring to derive informed decisions on weed management. The study of plant functional traits or weed biology providing knowledge for predicting weediness characteristics through growth and development is the third component. Each component or combined components could be used to reassess, deliberate and design weed management on farms with the objective of complementing and leveraging current weed controls for smallholders through examining the use of herbicides and fertilizers. A multidisplinary approach is recommendable for practical weed management.